Dental and oral management in beta major thalassemia in children - Eriska Riyanti (Universitas Padjadjaran, 2008)
Thalassemia beta major is a hereditary hemolytic anemia disease with various grades of severity, which can be found with no or less globin chain qualitative synthesis. The patient often experiences hepatosplenomegaly, growth retardation and bone disorder and the thalassemia facies/chipmunk face appearance. The orofacial manifestations of beta thalassemia major are prominent cheekbones and protrusive premaxillae due to erythroid hyperplasia with the depressed bridge of the nose. The dentition shows protrusion, flaring and spacing of the maxillary anterior teeth, open bite that leads to malocclusion. The anemic condition makes the patient is difficult to do all oral hygiene instruction thus caries index will increase. Dental practitioners especially pediatric dentists are required to have awareness towards the nature of the disease and its implication on dental care. Collaboration with haematologist has to be made in every dental treatment.